Simplifikasi Desain Robotic Arm 6-Sumbu untuk Penyemprotan Cat Otomotif Berbasis Benchmarking dan Autodesk Inventor - Alfred Ozzie Finerkwook; Gabriel Gabriel; Alvin D. P. Lie; Handi Wilujeng Nugroho; Kurniawan Hamidi; Rama Dani Eka Putra; Tessa Zulenia Fitri (UNIB Press, 2025)
This research aims to optimize the design of a 6-axis robotic Arm for spray painting processes in the automotive industry. The main problem identified is the complexity of the structure and the presence of non-functional components, which complicate the manufacturing process. Through benchmarking methods, analysis of the Bill of Materials (BoM), creation of an Operation Process Chart (OPC), and Assembly Chart (AC), the design was simplified without reducing its core functionality. Design development was carried out using Autodesk Inventor software to create a more efficient 3D model. An evaluation was conducted on the new design, including a Cost of Goods Manufactured (HPP) analysis to ensure cost efficiency. The research results show that eliminating non-functional parts improves production speed, reduces costs, and maintains the robotic Arm's balance and safety. Thus, the developed robotic Arm is simpler, more effective, and more economical to support increased industrial productivity.